Multidimensional Parental Involvement in Inclusive Education: A Multiple Case Study of Students with Special Needs - Sari, Nurul Maulida; Purwanta, Edi; Cahyani, Leni Ambar; Prihandini, Farah (FKIP Universitas Lampung, 2025)
Multidimensional Parental Involvement in Inclusive Education: A Multiple Case Study of Students with Special Needs. Objectives: This study aimed to explore parental involvement in inclusive school settings for children with special needs. Methods: A qualitative case study design was used. The participants in this research include parents, special education teachers, classroom teachers, principals, students, and close family members. The data collection techniques used in this study were in-depth interviews and documentation, with the researcher serving as the primary instrument. Data analysis was conducted in two stages: within-case analysis, interactive model (data condensation, data display, and conclusion drawing/verification), and cross-case analysis to compare engagement patterns across cases. To ensure the data validity, this research employed triangulation of sources and methods, thick description, and prolonged field engagement. Findings: The findings of this research revealed six main dimensions of parental involvement in inclusive education: (1) Parenting: teach discipline, autonomy, and provide environment that support children to study at home; (2) Communication, reflected in communication between parents and teachers regarding academic progress and performances; (3) Volunteering, involving parents’ participation in supporting schools activities; (4) Learning at Home, encompassing parents’ supervision of study routines, assignments, and exam preparation at home; (5) Decision-making, participate in decision-making concerning their child’s learning and broader school policies; and (6) Community Collaboration, includes partnerships with learning groups, disability service units, psychologists, and medical professionals. Conclusion: Parental involvement in inclusive schools for students with special needs is multidimensional. Hence, a strong collaboration between families, schools, and community institutions is needed. Parental engagement should be strengthened through open communication and cross-sector collaboration to improve educational quality. Inclusive education policies need to be put in place to enhance parental involvement in inclusive schools. Keywords: parental involvement, inclusive schools, children with special needs.